Specific Index Parameters definition for Quantitative Evaluation of the Dynamic Performance of the Electromagnetic Mechanism Topologies within Controllable Actuators - LOU Jie; SUN Bin; LI Qingmin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Fast electromagnetic drive mechanism shows broad application prospects in many areas, but there is still a lack of unified evaluation parameters as to evaluate the dynamic characteristics due to diversity and complexity of the mechanisms. Three interrelated evaluation parameters are presented for topology analysis, namely the electromagnetic force sensitivity coefficient, the initial time constant and the sensitivity contribution coefficient. The specific parameters based evaluation can provide a basis for structural performance assessment as well as topology optimization. Comparison between the dynamic parameters of the discoid repulsion mechanism and the solenoid thrust mechanism shows that, the discoid one is superior to the solenoid one. The proposed research is to establish a general methodology for topology analysis and optimization of the electromagnetic mechanisms. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2066